Exercise and consumption of herbal remedies decrease the risk of strokes in hypertension and diabetes mellitus patients undergoing a standard therapy - Akrom Akrom; Melisa Rizki (Pharmaciana, 2019)
Stroke is a serious problem faced worldwide. It can result in death, physical disability, and mental disability. Hypertension and Diabetes Mellitus (DM) patients are high-risk populations. The study attempted to determine the factors associated with the incidence of stroke in DM or hypertension outpatients. This analytic observational study used a case-control design and nonrandom sampling technique with consecutive sampling approach. With a 1:2 ratio, the subjects consisted of 49 stroke patients in the case group and 98 non-stroke patients (hypertensive) for the control group. Subjects were patients undergoing treatments at PKU Muhammadiyah Hospital in Bantul. Patient's lifestyle data were collected through face-to-face interviews with patients, while demographic information, diagnosis, and patient history were obtained from medical records using data retrieval forms (case record forms). The variable age was matched with sex to improve the efficiency and accuracy of the study. Data analysis included univariate (descriptive) analysis and bivariate analysis using the Chi-Square test. Factors associated with stroke incidence were smoking habit (OR = 2.940, CI: 1.314 <OR <6.576; P = 0.007), exercise routine (OR = 0.026, CI: 0.008 <OR <0.079, P = 0.000), high-fat food dietary pattern (OR = 3.629, CI: 1.119 <OR <11.766; P = 0.024), and the habit of consuming herbal remedies (OR = 0.299, CI: 0.107 <OR <0.833; P = 0.016). Â For hypertension or DM patients who took standard therapy at PKU Muhammadiyah Hospital in Bantul, smoking and fatty food consumption increased the risk of stroke, whereas physical exercise and herbs consumption habits reduced it.